«Oser dire non!», une action flash de prévention des conduites dopantes sportives - Laure, P.; Favre, A. (Science & Sports, 2016)
Objective: To measure the efficiency of a short, one-off prevention action of doping behaviours among adolescents in a sport excellence cursus (in France, training structures which prepare access to high level sport). Methods: One hundred and nine young athletes (girls: 53%), aged 14.4 ± 1.2 y.o. (average ± standard deviation), set in little groups (less than 15 people). The aim of the two-hours-long session was to enhance adolescents` self-assertion (to know how to refuse a doping incitement, to say no and to keep this answer, etc. by the way of role playing games) and to give information on self-medication. The action was structured around the engaging communication paradigm. Stakeholders were two. Results: Each youth took actively part in the action. At the end of the sessions, 100% stated that they were able to say no to a forbidden substance, and 64% thought they were totally able to ask for help (girls were less positive about that: 45% versus 86% of boys, P < 0.001). Lastly, 98% stated that the session help them to reach these results. Conclusion: A short one-off action based upon skills training education may contribute to enhance adolescents` abilities to face a situation where someone offers them an unwanted substance. Its interest is to be participative, based on games and pleasure, and to need no specific tool.